Ten Years Of Preventive Geriatric Services In The City Of Germiston - C.A. Erasmus (AOSIS, 1979)
The deficiencies in the health care delivery system for the aged in our various population groups to a large extent arises as a result of the three tier system of health responsibility in operation in South Africa up to the present. The Health Act No. 63 of 1977 will perhaps remedy this situation once it is fully implemented but at present there are very definite shortcomings in the existing medical services available to the aged. The quality of these medical services also varies from Province to Province and also within individual Provinces due to the absence of a national policy based on recognised principles of geriatric care.